Economic burden and its associated factors of hospitalized patients infected with A (H7N9) virus: a retrospective study in Eastern China, 2013–2014. Issue 1 (December 2016) - Huo, Xiang; Chen, Li-Ling; Hong, Lei; Xiang, Lun-Hui; Tang, Fen-Yang; Chen, Shan-Hui; Gao, Qiang; Chen, Cong; Dai, Qi-gang; Sun, Chuan-Wu; Xu, Ke; Dai, Wen-Jun; et al.
Abstract Background H7N9 continues to cause human infections and remains a pandemic concern. Understanding the economic impacts of this novel disease is important for making decisions on health resource allocation, including infectious disease prevention and control investment. However, there are limited data on such impacts. Methods Hospitalized laboratory-confirmed H7N9 patients or their families in Jiangsu Province of China were interviewed. Patients' direct medical costs of hospitalization were derived from their hospital bills. A generalized linear model was employed to estimate the mean direct medical costs of patients with different characteristics. Results The mean direct cost of hospitalization for H7N9 was estimated to be ¥ 71 060 (95 % CI, 48 180–104 820), i.e., US 10 996 (95 % CI, 7 455–16 220), and was ¥12 060 (US 1 861), ¥136 120 (US 21 001) and ¥218 610 (US 33 728) for those who had mild or severe symptoms or who died, respectively. The principal components of the total fees differed among patients with different disease severity, although medication fees were always the largest contributors. Disease severity, proportion of reimbursement and family member monthly average income were identified as the key factors that contributed to a patient's direct medical cost of hospitalization. Conclusions The direct medical costs of hospitalized patients with H7N9 are significant, and far surpass the annual per capita income of Jiangsu Province, China. The influencing factors identified should be taken into account when developing related health insurance policies and making health resource allocation. Trial registration Not applicable. This is a survey study with no health care intervention implemented on human participants.